Low Bit-Rate Parametric Coding - Djadjat Sudaradjat; Andi Rosano (Paradigma, 2022)
With a low bit rate will be obtained savings in the use of bandwidth transmission channels and memory. In coding the human voice signal, an artificial voice-producing model is made to obtain a low bit rate, which is known as the parametric coding method. With the parametric coding method, the human voice signal can produce a lower bit rate than the waveform coding method. For example, the waveform coding method will be limited by a minimum sampling frequency which according to the Shannon-Nyquist theorem states that so that no information is lost when sampling the signal, the sampling speed must be at least twice the bandwidth of the signal. Thus, the lowest bit rate waveform encoding that can be achieved is by the Delta Modulation system which is 8 Kbit/sec. While the signal parametric coding can achieve a lower bit rate of 2.4 Kbit/sec by the LPC (Linear Predictive Coding) system.